Clinical Practice Guidelines for postoperative period of thoracic surgery. - Frank Carlos Alvarez Li; Daniel Olivera Fajardo; Félix Molina Díaz (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Clinical Practice Guidelines for postoperative period of thoracic surgery. It is the period between the suture of the surgical wound and the total rehabilitation of the patient, which usually occurs in the Intensive Care Unit. This document includes a review and update of the main aspects such as classification, postoperative treatment, stressing the actions to face any complication. It includes assessment guidelines focused on the most important aspects to be accomplished.